..

Алгебра visibility 77 просмотров

Вопрос:

преобразовать(1)/(2) + ( (3m)/(1-3m) + (2m)/(3m+1) ) *

Ответы и объяснения от Мегамозга

Мегамозг

1/2 +  (3m * ( 1+3m) +2m * (1 -3m))/ (1-9m^2) * (3m-1)^2 / (2m*(3m+5) =1/2 + (3m+9m^2+2m-6m^2)/(1-9m^2) * (3m-1)^2 /2m(3m+5) =1/2 + (5m+3m^2)/ (1-9m^2) * (3m-1)^2 / 2m (3m+5) =1/2 + (m*95+3m)*(3m-1)^2 )/ (2m(3m+5)*(1-9m^2) =1/2+(3m-1)^2 / (-2 *( 3m-1)(1+3m))= 1/2+ (3m-1)/(-2(1+3m)) = (-(1+3m)+3m-1))/(-2(1+3m)) = (-2)/(-2(1+3m) = 1/ (1+3m) у меня так получилось)

Ответить на вопрос


Adblock
detector